An In-depth Analysis of Majoon Zabeeb, an Enduring Polyherbal Unani Formulation for Epilepsy - Alam, Md. A.; Zakir, Mohammad; Khatoon, Faiza; Ahmad, Waish; Minhajuddin, Ahmed (Current Traditional Medicine, 2023)
Unani Medicine System is one of the oldest systems, with its potent and effective drugs from animal, plant, and mineral sources. Over 2400 years ago, Hippocrates, the founder of medicine, practiced it; however, his medicine includes many ancient Egyptian medications and important components of ancient Mesopotamian customs and traditions. Neurological problems are a significant cause of death, comprising 12% of all deaths globally. Sar' is used for epilepsy in USM, which means falling. Convulsions occur after the patient has fallen due to partial occlusion in the passage of Rūh NafsĦ#129;nī (psychic pneuma). A vast number of single and multi-ingredient medicines were referenced for epilepsy treatment. Majoon Zabeeb (MZ) is possibly the most presumed polyherbal preparation used in epilepsy. This polyherbal compound has eight components used as a strong anticonvulsant, antispasmodic, antioxidant, deobstruent, memory enhancer, neuroprotective, nervine tonic, and anti-inflammatory agent.
Keywords: neurological disorder